Silicon dioxide polishing solution and preparation method thereof

By connecting the mesh particles and spherical particles with a high hydroxyl content, the existing silica polishing liquid has low efficiency and scratches, and the high-efficiency and low scratch polishing effect is achieved.

CN119899592APending Publication Date: 2025-04-29YONGJIANG LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411998128.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing silica polishing liquid is inefficient and easily causes scratches during the polishing process, and cannot effectively increase the polishing rate.

Method used

Silica composite particles including mesh particles and spherical particles are used to connect spherical particles with mesh particles through silane coupling agent to increase the hydroxyl content on the surface of the composite particles and increase the chemical force of the polishing liquid.

Benefits of technology

The polishing efficiency of silica polishing liquid is significantly improved, the risk of scratches is reduced, and the material removal rate is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225363560000132
    Figure BDA0005225363560000132
  • Figure HDA0005225363700000011
    Figure HDA0005225363700000011
  • Figure HDA0005225363700000012
    Figure HDA0005225363700000012
Patent Text Reader

Abstract

The invention belongs to the technical field of semiconductor chemical mechanical polishing, and particularly discloses a silicon dioxide polishing solution and a preparation method thereof.The silicon dioxide polishing solution comprises silicon dioxide composite particles, the silicon dioxide composite particles comprise net-shaped particles and spherical particles, and the spherical particles are connected to the surfaces of the net-shaped particles; the hydroxyl content in the silicon dioxide composite particles is greater than or equal to 0.001 mol / g silicon oxide. Therefore, the silicon dioxide polishing solution is relatively high in polishing efficiency and is not easy to cause scratches.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of semiconductor chemical mechanical polishing, and specifically relates to a silicon dioxide polishing liquid and a preparation method thereof. Background Art

[0002] In the current polishing technology field, colloidal silica, as a widely used grinding medium, has disadvantages such as low polishing efficiency and easy scratching. Most of the related technologies adjust the morphology of particles to increase the contact area and friction between particles, thereby improving the physical effect of particles during polishing. However, the polishing rate is limited and it is more likely to cause scratches. Therefore, silica polishing technology needs to be further improved. Summary of the invention

[0003] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present application proposes a silicon dioxide polishing liquid with high polishing efficiency and a preparation method thereof.

[0004] In a first aspect, the present application provides a silicon dioxide polishing liquid, comprising silicon dioxide composite particles, wherein the silicon dioxide composite particles include mesh particles and spherical particles, wherein the spherical particles are connected to the surface of the mesh particles, and the hydroxyl content in the silicon dioxide composite particles is greater than or equal to 0.001 mol / g silicon oxide. Thus, the silicon dioxide polishing liquid described in the present application has a high polishing efficiency and is not easy to cause scratches.

[0005] In some embodiments, the spherical particles are connected to the surface of the mesh particles via a silane coupling agent, thereby further improving the polishing efficiency of the silicon dioxide polishing liquid.

[0006] In some embodiments, the general formula of the silane coupling agent is RSiX3, wherein R is selected from at least one of amino, thiol, vinyl, epoxy, cyano and methylvinyloxy, and X is selected from at least one of methoxy and ethoxy. Thus, the material source is wide, the cost is low, and the surface of the spherical particles can be modified.

[0007] In some embodiments, the molar ratio of the silane coupling agent to the spherical particles is 3: 100 to 8: 100. Within the above molar ratio range, it is advantageous to connect the silane coupling agent to the surface of the spherical particles, and then the spherical particles can be connected to the surface of the mesh particles through the silane coupling agent.

[0008] In some embodiments, the specific surface area of ​​the silica composite particles is 300 m 2 / g~400m 2 / g, the specific surface area of ​​the mesh particles is 400m 2 / g~500m 2 / g, the specific surface area of ​​the spherical particles is 100m 2 / g~200m 2 / g. This can increase the contact area between particles and silicon wafers during polishing, and at the same time help expose unreacted hydroxyl groups to promote chemical forces during the polishing process.

[0009] In some embodiments, the mass ratio of the spherical particles to the mesh particles is 2:1 to 4:1. If the mass ratio is too small, the mechanical force during polishing is small and the polishing effect is not ideal; if the mass ratio is too large, the number of hydroxyl groups is insufficient, resulting in an insignificant improvement in polishing efficiency. Within the above mass ratio range, it is beneficial to improve the overall polishing effect of the silicon dioxide polishing liquid.

[0010] In some embodiments, the silicon dioxide polishing liquid further comprises an oxidant, a pH adjuster, a dispersant, and a second inorganic solvent, thereby further improving the polishing efficiency of the silicon dioxide polishing liquid.

[0011] In some embodiments, the oxidant includes at least one of hydrogen peroxide and potassium permanganate, thereby promoting the redox reaction and improving the polishing efficiency.

[0012] In some embodiments, the pH adjuster includes at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, triethanolamine, diethanolamine, ethylenediamine, triethylamine, potassium hydroxide, sodium hydroxide, ammonia, hydrochloric acid, oxalic acid, formic acid, acetic acid, nitric acid and L-tartaric acid. The pH directly affects the solubility of silicon oxide and the interaction between silicon dioxide particles and silicon wafers, thereby greatly affecting the polishing rate.

[0013] In some embodiments, the dispersant includes at least one of a polymer dispersant, a water-soluble anionic dispersant, and a water-soluble nonionic dispersant; wherein the polymer dispersant includes at least one of an acrylic acid ammonium salt and a special polycarboxylic acid polymer dispersant, the water-soluble anionic dispersant includes at least one of lauryl sulfate triethanolamine, ammonium lauryl sulfate, and polyoxyethylene alkyl ether sulfate triethanolamine, and the water-soluble nonionic dispersant includes at least one of polyoxyethylene lauryl ether, polyoxyethylene hexadecyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene higher alcohol ether, and polyoxyethylene octylphenyl ether. Thus, the material source is wide, and the dispersibility of the silicon dioxide polishing liquid can be improved.

[0014] The second aspect of the present application provides a method for preparing a silicon dioxide polishing liquid, comprising:

[0015] mixing silane with a first inorganic solvent so that the silane is hydrolyzed to obtain a gel;

[0016] mixing the gel with a base to obtain mesh particles;

[0017] connecting spherical particles to the surface of the mesh particles to obtain silica composite particles;

[0018] The silica composite particles are mixed with an oxidant, a pH adjuster, a dispersant, and a second inorganic solvent to obtain the silica polishing liquid.

[0019] The present application increases the number of hydroxyl groups on the surface of silicon dioxide composite particles and utilizes the reaction between hydroxyl groups and silicon oxide during polishing to increase the chemical force of polishing, thereby increasing the polishing rate.

[0020] In some embodiments, the silane includes at least one of tetramethoxysilane, tetraethoxysilane and tetrabutoxysilane. Thus, the material source is wide and the cost is low.

[0021] In some embodiments, the mass concentration of the silane in the first inorganic solvent is 3% to 12%. Too high a silane content will result in a network structure that is too strong to be untied, and too low a silane concentration will result in a too long gelling time. A silane concentration within the above range is conducive to improving the reaction efficiency and making the network structure easy to untie.

[0022] In some embodiments, the silane and the first inorganic solvent are mixed for a first stirring, and the first stirring temperature is 15° C. to 50° C., the rotation speed is 100 rpm to 500 rpm, and the time is 0.5 h to 8 h, which is conducive to promoting the reaction and improving the hydrolysis efficiency of the silane.

[0023] In some embodiments, the viscosity of the gel is 10 mPas to 100 mPas. If the viscosity is too low, the network structure is not formed; if the viscosity is too high, the network structure is too strong and cannot be untied and directly gelled. When the viscosity of the gel is within the above range, it is conducive to the untiing of the network structure.

[0024] In some embodiments, the base includes at least one of potassium hydroxide, sodium hydroxide, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, triethanolamine, diethanolamine, triethylamine, ethylenediamine, triethylenediamine, pyridine, and 3-ethoxypropylamine. Thus, the material source is wide, the cost is low, and it is conducive to destroying the network structure.

[0025] In some embodiments, the molar ratio of the base to the silane is 3:100 to 16:100. If the amount of base is too little, the network structure cannot be destroyed; if the amount of base is too much, it will cause a waste of raw materials. Within the above ratio range, it is conducive to destroying the network structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM photograph of the mesh particles in Example 1 of the present application.

[0027] Figure 2 This is a SEM photograph of the composite particles in Example 1 of the present application.

[0028] Figure 3 This is a SEM photograph of the composite particles in Example 2 of the present application.

[0029] Figure 4 This is a SEM photograph of the spherical particles in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0030] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0031] In a first aspect, the present application proposes a silica polishing liquid, comprising silica composite particles, wherein the silica composite particles include mesh particles and spherical particles, wherein the spherical particles are connected to the surface of the mesh particles, and the hydroxyl content in the silica composite particles is greater than or equal to 0.001 mol / g silica.

[0032] The hydroxyl content on the surface of the silicon dioxide composite particles in the present application is greater than or equal to 0.001mol / g silicon oxide, and a large amount of unreacted hydroxyl groups make the silicon dioxide composite particles have strong reactivity. Hydroxyl groups can react with hydronium under acidic conditions to make the surface of the mesh particles positively charged, or dehydrate by reacting with hydrogen bonds on the wafer surface silicon oxide, so that the mesh particles are connected to the wafer surface silicon oxide, thereby being more easily mechanically removed. However, the particle size of the mesh particles is small, and the mechanical force is small during the polishing process. Therefore, the silicon dioxide composite particles of the present application have both mesh particles and spherical particles, and the mechanical force of the mesh particles can be increased by synergistic action, thereby improving the polishing efficiency of the silicon dioxide polishing liquid.

[0033] In some embodiments, the spherical particles are connected to the surface of the mesh particles via a silane coupling agent, thereby further improving the polishing efficiency of the silicon dioxide polishing liquid.

[0034] In some embodiments, the general formula of the silane coupling agent is RSiX3; wherein R is selected from at least one of amino, thiol, vinyl, epoxy, cyano and methylvinyloxy; and X is selected from at least one of methoxy and ethoxy. For example, the silane coupling agent can be thiolpropyltrimethoxysilane. As a result, the material source is wide and the cost is low, and the surface of the spherical particles can be modified. Subsequently, the mesh particles and the spherical particles are connected to each other through the surface-modified R groups.

[0035] In some embodiments, the molar ratio of the silane coupling agent to the spherical particles is 3:100 to 8:100, for example, 3:100, 4:100, 5:100, 6:100, 7:100 or 8:100, etc. The amount of the silane coupling agent is proportional to the solid content of the silica spherical particles in the solution. Within the above molar ratio range, it is beneficial to connect the silane coupling agent to the surface of the spherical particles, and then the spherical particles can be connected to the surface of the mesh particles through the silane coupling agent.

[0036] In some embodiments, the specific surface area of ​​the silica composite particles is 300 m 2 / g~400m 2 / g, for example, 300m 2 / g, 310m 2 / g, 320m 2 / g, 330m 2 / g, 340m 2 / g, 350m 2 / g, 360m 2 / g, 370m 2 / g、380m 2 / g, 390m 2 / g or 400m 2 / g, etc.; the specific surface area of ​​the mesh particles is 400m 2 / g~500m 2 / g, for example, 400m 2 / g, 410m 2 / g, 420m 2 / g, 430m 2 / g, 440m 2 / g, 450m 2 / g, 460m 2 / g, 470m 2 / g, 480m 2 / g, 490m 2 / g or 500m 2 / g, etc.; the specific surface area of ​​the spherical particles is 100m 2 / g~200m 2 / g, for example, 100m 2 / g, 110m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g, 170m 2 / g, 180m 2 / g, 190m2 / g or 200m 2 / g, etc. Among them, the specific surface area of ​​the mesh particles is greater than the specific surface area of ​​the spherical particles, that is, the particle size of the mesh particles is smaller than that of the spherical particles. In this article, specific surface area refers to the sum of the surface areas of particles per unit mass, and the test method is to use BET specific surface area analysis. During the polishing process, the larger the specific surface area of ​​the particles, the larger the contact area between the particles and the silicon wafer, which increases the mechanical force. The hydroxyl content and specific surface area are also proportional. A high specific surface area is conducive to the exposure of unreacted hydroxyls to the surface, thereby promoting the chemical action of the silica composite particles during polishing.

[0037] In some embodiments, the mass ratio of the spherical particles to the mesh particles is 2:1 to 4:1, for example, 2:1, 3:1 or 4:1. If the mass ratio is too small, the mechanical force during polishing is small and the polishing effect is not ideal; if the mass ratio is too large, the number of hydroxyl groups is insufficient, resulting in an insignificant improvement in polishing efficiency. Within the above mass ratio range, it is beneficial to improve the overall polishing effect of the silicon dioxide polishing liquid.

[0038] In some embodiments, the silicon dioxide polishing liquid further comprises an oxidant, a pH adjuster, a dispersant, and a second inorganic solvent, thereby further improving the polishing efficiency of the silicon dioxide polishing liquid.

[0039] In some embodiments, the oxidant includes at least one of hydrogen peroxide and potassium permanganate, thereby promoting the redox reaction and improving the polishing efficiency.

[0040] In some embodiments, the pH adjuster includes at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, triethanolamine, diethanolamine, ethylenediamine, triethylamine, potassium hydroxide (KOH), sodium hydroxide (NaOH), ammonia water, hydrochloric acid, oxalic acid, formic acid, acetic acid, nitric acid and L-tartaric acid. Thus, the material source is wide and the polishing efficiency can be improved.

[0041] In some embodiments, the dispersant includes at least one of a polymer dispersant, a water-soluble anionic dispersant, and a water-soluble nonionic dispersant; wherein the polymer dispersant includes at least one of an acrylic acid ammonium salt and a special polycarboxylic acid polymer dispersant, the water-soluble anionic dispersant includes at least one of lauryl sulfate triethanolamine, ammonium lauryl sulfate, and polyoxyethylene alkyl ether sulfate triethanolamine, and the water-soluble nonionic dispersant includes at least one of polyoxyethylene lauryl ether, polyoxyethylene hexadecyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene higher alcohol ether, and polyoxyethylene octylphenyl ether. Thus, the material source is wide, and the dispersibility of the silicon dioxide polishing liquid can be improved.

[0042] The second aspect of the present application provides a method for preparing a silicon dioxide polishing liquid, comprising:

[0043] S1: mixing silane with a first inorganic solvent so that the silane is hydrolyzed to obtain a gel.

[0044] In some embodiments, the silane includes at least one of tetramethoxysilane (TMOS), tetraethoxysilane (TEOS) and tetrabutoxysilane (TPOS). The silane hydrolyzes in the first inorganic solvent to slowly form a gel, forming a gel with a network cross-linked structure. By breaking part of the network structure and converting the gel into a stable silica sol, network particles with a high specific surface area can be obtained.

[0045] Among them, silane reacts with the first inorganic solvent to generate silica monomers and methanol, and the hydrolyzed silica monomers will polymerize under the influence of factors such as pH, temperature, and concentration. When enough particles are connected to each other, a network structure will be formed, and the gaps in the structure will be filled with water and methanol, so that the solution will no longer flow (gel).

[0046] In some embodiments, based on the mass of the first inorganic solvent, the mass concentration of the silane is 3% to 12%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11% or 12%. If the silane content is too high, the network structure will be too strong to be untied, and if the silane concentration is too low, the gelation time will be too long. Therefore, a suitable silane concentration is conducive to improving the reaction efficiency and making the network structure easy to be untied.

[0047] In some embodiments, the silane is mixed with the first inorganic solvent for a first stirring, the temperature of the first stirring is 15°C to 50°C, for example, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, the speed is 100rpm to 500rpm, for example, 100rpm, 200rpm, 300rpm, 400rpm or 500rpm, and the time is 0.5h to 8h, for example, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h. Within the above reaction conditions, it is beneficial to promote the reaction and improve the hydrolysis efficiency of silane. Specifically, the prepared hydrolyzate can be placed in a water bath, the temperature is set at 15°C to 50°C, and a stirring paddle is used for mechanical stirring for a certain period of time until the viscosity reaches 10mPas to 100mPas.

[0048] In some embodiments, at 25° C., the viscosity of the gel is 10 mPas to 100 mPas, for example, 10 mPas, 20 mPas, 30 mPas, 40 mPas, 50 mPas, 60 mPas, 70 mPas, 80 mPas, 90 mPas or 100 mPas, etc. The viscosity of the gel is monitored by a viscometer. When the viscosity of the gel is within the above range, it is beneficial for the network structure to be untied.

[0049] S2: mixing the gel with a base to obtain network particles.

[0050] In some embodiments, the base includes at least one of potassium hydroxide, sodium hydroxide, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, triethanolamine, diethanolamine, triethylamine, ethylenediamine, triethylenediamine, pyridine, and 3-ethoxypropylamine. Thus, the material source is wide, the cost is low, and it is conducive to destroying the network structure.

[0051] In some embodiments, the molar ratio of the base to the silane is 3:100 to 16:100, for example, 3:100, 5:100, 7:100, 9:100, 11:100, 13:100 or 16:100, etc. Among them, the amount of base used is related to the amount of silane used. If the base is too little, the network structure cannot be destroyed; if the amount of base is too much, it will cause a waste of raw materials. Within the above-mentioned proportion range, it is beneficial to destroy the network structure. In some specific examples, the base needs to be preheated to 60°C to 90°C (such as 60°C, 70°C, 80°C or 90°C, etc.). During the experiment, it was observed that the hot alkali is very effective in destroying the network structure. Heating the base is conducive to the complete destruction of the network structure.

[0052] In some embodiments, mixing the gel with the base comprises: adding the gel to the base via a peristaltic pump. At high pH and high temperature, silica will dissolve in the base, causing the network structure to break apart.

[0053] S3: connecting the spherical particles to the surface of the mesh particles to obtain silica composite particles.

[0054] In some embodiments, connecting the spherical particles to the surface of the mesh particles includes: connecting the spherical particles and the mesh particles using a silane coupling agent. Specifically, the silane coupling agent and the spherical particles can be mixed for a second stirring to obtain a mixed solution of the silane coupling agent and the spherical particles, the temperature of the second stirring is 35°C to 85°C, for example, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 85°C, etc., the rotation speed is 100rpm to 500rpm, for example, 100rpm, 200rpm, 300rpm, 400rpm or 500rpm, etc., the time is 1h to 3h, for example, 1h, 1.5h, 2h, 2.5h or 3h, etc.; then the mesh particles are mixed with the mixed solution of the silane coupling agent and the spherical particles for a third stirring, and the mesh particles can be dropped into the mixed solution of the silane coupling agent and the spherical particles. , the dropping rate is maintained at 0.5 g / min to 10 g / min (such as 0.5 g / min, 1 g / min, 2 g / min, 3 g / min, 4 g / min, 5 g / min, 6 g / min, 7 g / min, 8 g / min, 9 g / min or 10 g / min, etc.), the temperature of the third stirring is 35°C to 85°C, such as 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 85°C, etc., the speed is 100 rpm to 500 rpm, such as 100 rpm, 200 rpm, 300 rpm, 400 rpm or 500 rpm, etc., and the time is 1 h to 3 h, such as 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc. Thus, the reaction efficiency can be improved, and the spherical particles can be more efficiently connected to the surface of the mesh particles.

[0055] It can be understood that the spherical particles are connected to the mesh particles through covalent bonds after being modified by the surfactant, and the chemical and physical forces of the silica composite particles during polishing can be adjusted by adjusting the ratio of the spherical particles to the mesh particles.

[0056] S4: mixing the silica composite particles with an oxidant, a pH adjuster, a dispersant, and a second inorganic solvent to obtain the silica polishing liquid.

[0057] As an example, the silica composite particles, the oxidant, the dispersant, and the second inorganic solvent (such as deionized water) may be mixed in a certain ratio, and the pH value may be adjusted to 4-6 with a pH adjuster.

[0058] The embodiments of the present application are described in detail below.

[0059] Example 1

[0060] (1) 114.04 g of tetramethoxysilane and 185.96 g of ultrapure water were mixed to obtain 300 mL of a 10 wt% hydrolyzate;

[0061] (2) diluting potassium hydroxide with water to a mass concentration of 4%;

[0062] (3) hydrolyzing the hydrolyzate at 15° C. and 250 rpm for 6 h until the viscosity reaches 9.78 mPas;

[0063] (4) The hydrolyzate after the reaction was added dropwise to 36.55 g of the 4 wt% potassium hydroxide solution obtained above at 85°C, and the reaction was continued for 5 min and 2 h to obtain a network particle solution. The SEM photo is shown in Figure 1 ;

[0064] (5) 100 g of 7 wt% spherical particle solution and 0.686 thiol propyl trimethoxysilane were mixed and heated to 85°C and stirred at 250 rpm for 2 h. After the reaction was completed, 35 g of 10 wt% mesh particle solution was added dropwise for 1 h. After the addition was completed, the mixture was aged for 2 h to obtain a composite particle solution. The SEM photo is shown in FIG. Figure 2 ;

[0065] (6) 113.72 g of the composite particle solution, 1.494 g of 20 wt% hydrogen peroxide, 1.25 g of polyoxyethylene lauryl ether and 323.536 g of deionized water were mixed to obtain 440 g of a mixed solution having a solid content of about 2%. The pH was adjusted to 4.8 with 5 wt% dilute nitric acid to obtain a polishing solution 1.

[0066] Example 2

[0067] (1) 114.04 g of tetramethoxysilane and 185.96 g of ultrapure water were mixed to obtain 300 mL of a 10 wt% hydrolyzate;

[0068] (2) diluting potassium hydroxide with water to a mass concentration of 4%;

[0069] (3) hydrolyzing the hydrolyzate at 15° C. and 250 rpm for 6 h until the viscosity reaches 9.78 mPas;

[0070] (4) adding the hydrolyzate after the reaction to 36.55 g of the 4 wt % potassium hydroxide solution obtained above at 85° C. for 5 min and then continuing the reaction for 2 h to obtain a network particle solution;

[0071] (5) 100 g of 7 wt% spherical particles and 0.686 thiol propyl trimethoxysilane were mixed and heated to 85°C and stirred at 250 rpm for 2 h. After the reaction was completed, 70 g of 10 wt% mesh particle solution was added dropwise for 1 h. After the addition was completed, the composite particle solution was aged for 2 h to obtain a SEM photo. Figure 3 ;

[0072] (6) 107.29 g of the composite particle solution, 1.494 g of 20 wt% hydrogen peroxide, 1.25 g of polyoxyethylene lauryl ether and 323.536 g of deionized water were mixed to obtain 440 g of a mixed solution having a solid content of about 2%. The pH was adjusted to 4.8 with 5 wt% dilute nitric acid to obtain polishing solution 2.

[0073] Example 3

[0074] (1) 114.04 g of tetramethoxysilane and 185.96 g of ultrapure water were mixed to obtain 300 mL of a 10 wt% hydrolyzate;

[0075] (2) diluting ethylenediamine with water to a mass concentration of 4%;

[0076] (3) hydrolyzing the hydrolyzate at 50° C. and a stirring speed of 100 rpm for 8 h until the viscosity reaches 50 mPas;

[0077] (4) dripping the hydrolyzate after the reaction into 36.55 g of 4 wt% ethylenediamine solution at 85° C., adding for 5 min and then continuing the reaction for 1 h to obtain a network particle solution;

[0078] (5) 100 g of spherical 7 wt% particles and 0.686 thiolpropyltrimethoxysilane were mixed and heated to 85°C, and stirred at 250 rpm for 2 h. After the reaction was completed, 25 g of 10 wt% mesh particle solution was added dropwise for 1 h. After the addition was completed, the mixture was aged for 2 h to obtain a composite particle solution;

[0079] (6) 113.72 g of the composite particle solution, 1.494 g of 20 wt% potassium permanganate, 1.25 g of triethanolamine lauryl sulfate and 323.536 g of deionized water were mixed to obtain 440 g of a mixed solution having a solid content of about 2%. The pH was adjusted to 4.8 with 5 wt% dilute nitric acid to obtain polishing solution 3.

[0080] Example 4

[0081] (1) 114.04 g of tetrabutoxysilane and 185.96 g of ultrapure water were mixed to obtain 300 mL of a 10 wt% hydrolyzate;

[0082] (2) diluting ethylenediamine with water to a mass concentration of 4%;

[0083] (3) hydrolyzing the hydrolyzate at 15° C. and a stirring speed of 500 rpm for 6 h until the viscosity reaches 10 mPas;

[0084] (4) dripping the hydrolyzate after the reaction into 36.55 g of 4 wt% pyridine solution at 85° C., adding for 5 min and then continuing the reaction for 1 h to obtain a network particle solution;

[0085] (5) 100 g of 7 wt% spherical particles and 0.686 thiolpropyltrimethoxysilane were mixed and heated to 65°C and stirred at 250 rpm for 1 hour. After the reaction was completed, 50 g of 10 wt% mesh particle solution was added dropwise for 1 hour. After the addition was completed, the mixture was aged for 3 hours to obtain a composite particle solution;

[0086] (6) 113.72 g of the composite particle solution, 1.494 g of 20 wt% potassium permanganate, 1.25 g of triethanolamine lauryl sulfate and 323.536 g of deionized water were mixed to obtain 440 g of a mixed solution having a solid content of about 2%. The pH was adjusted to 4.8 with 5 wt% oxalic acid to obtain polishing solution 4.

[0087] Example 5

[0088] (1) 114.04 g of tetraethoxysilane and 185.96 g of ultrapure water were mixed to obtain 300 mL of a 10 wt% hydrolyzate;

[0089] (2) diluting triethylenediamine with water to a mass concentration of 4%;

[0090] (3) hydrolyzing the hydrolyzate at 25° C. and a stirring speed of 250 rpm for 0.5 h until the viscosity reaches 100 mPas;

[0091] (4) adding the hydrolyzate after the reaction to 36.55 g of the 4 wt% triethylene dichloride solution obtained above at 85° C. for 5 min and then continuing the reaction for 2 h to obtain a network particle solution;

[0092] (5) 100 g of 7 wt% spherical particles and 0.686 thiolpropyltrimethoxysilane were mixed and heated to 35°C, and stirred at 250 rpm for 3 h. After the reaction was completed, 35 g of 10 wt% mesh particle solution was added dropwise for 1 h. After the addition was completed, the mixture was aged for 1 h to obtain a composite particle solution;

[0093] (6) 113.72 g of the composite particle solution, 1.494 g of 20 wt% hydrogen peroxide, 1.25 g of ammonium acrylate and 323.536 g of deionized water were mixed to obtain 440 g of a mixed solution having a solid content of about 2%. The pH was adjusted to 4.8 with 5 wt% formic acid to obtain a polishing solution 5.

[0094] Comparative Example 1

[0095] 125.71 g of silica spherical particle solution (concentration 7 wt %, see photo) was added Figure 4), 1.494 gwt 20% hydrogen peroxide, 1.25 g polyoxyethylene lauryl ether and 323.536 g deionized water were mixed to obtain 440 g of a mixed solution with a solid content of about 2%. The pH was adjusted to 4.8 with 5 wt % dilute nitric acid to obtain Comparative Example 1.

[0096] Comparative Example 2

[0097] (1) 114.04 g of tetramethoxysilane and 185.96 g of ultrapure water were mixed to obtain 300 mL of a 10 wt% hydrolyzate;

[0098] (2) diluting potassium hydroxide with water to a mass concentration of 4%;

[0099] (3) hydrolyzing the hydrolyzate at 15° C. and 250 rpm for 6 h until the viscosity reaches 9.78 mPas;

[0100] (4) The hydrolyzate after the reaction was completed was dripped into 36.55 g of the 4 wt % potassium hydroxide solution obtained above at 85° C., and the reaction was continued for 2 h after the dripping for 5 min to obtain a network particle solution, thereby obtaining Comparative Example 2.

[0101] The test method is as follows:

[0102] 1) Polishing test: The polishing machine is set to a pressure of 2 psi, a flow rate of 100 g / min, and a polishing time of 2 min. The thickness of silicon oxide on the surface of the silicon wafer is tested using a film thickness meter. By comparing the change in silicon oxide thickness before and after polishing, the material removal rate (MRR) is calculated using the following formula: d pre is the thickness before polishing (nm), d af is the thickness after polishing (nm), t is the time (min);

[0103] 2) Particle size test: tested by Malvern particle size analyzer.

[0104] The test results are shown in Table 1:

[0105] Table 1 Material removal rate and particle size

[0106]

[0107] It can be seen from Table 1 that the material removal rates of Examples 1 to 5 are significantly higher than those of Comparative Examples 1 to 2, indicating that the polishing efficiency of the silicon dioxide polishing liquid of the present application is improved.

[0108] In the description of the present application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0109] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0110] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A silicon dioxide polishing liquid, characterized in that: The invention comprises silicon dioxide composite particles, wherein the silicon dioxide composite particles comprise mesh particles and spherical particles, the spherical particles are connected to the surface of the mesh particles, and the hydroxyl content in the silicon dioxide composite particles is greater than or equal to 0.001 mol / g silicon oxide.

2. The silicon dioxide polishing liquid according to claim 1, characterized in that The spherical particles are connected to the surface of the mesh particles via a silane coupling agent; and / or The general formula of the silane coupling agent is RSiX3; wherein R is selected from at least one of amino, mercapto, vinyl, epoxy, cyano and methylvinyloxy; X is selected from at least one of methoxy and ethoxy; and / or The molar ratio of the silane coupling agent to the spherical particles is 3:100 to 8:

100.

3. The silicon dioxide polishing liquid according to claim 1, characterized in that The specific surface area of ​​the silicon dioxide composite particles is 300 m 2 / g~400m 2 / g; and / or The specific surface area of ​​the mesh particles is 400 m 2 / g~500m 2 / g; and / or The specific surface area of ​​the spherical particles is 100 m 2 / g~200m 2 / g.

4. The silicon dioxide polishing liquid according to claim 1, characterized in that The mass ratio of the spherical particles to the mesh particles is 2:1 to 4:

1.

5. The silicon dioxide polishing liquid according to claim 1, characterized in that The silicon dioxide polishing liquid further includes an oxidant, a pH adjuster, a dispersant and a second inorganic solvent.

6. The silicon dioxide polishing liquid according to claim 5, characterized in that The oxidant comprises at least one of hydrogen peroxide and potassium permanganate; and / or The pH regulator comprises at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, triethanolamine, diethanolamine, ethylenediamine, triethylamine, potassium hydroxide, sodium hydroxide, ammonia water, hydrochloric acid, oxalic acid, formic acid, acetic acid, nitric acid and L-tartaric acid; and / or The dispersant includes at least one of a polymer dispersant, a water-soluble anionic dispersant and a water-soluble nonionic dispersant.

7. The silicon dioxide polishing liquid according to claim 6, characterized in that The polymer dispersant includes at least one of an ammonium acrylate salt and a special polycarboxylic acid type polymer dispersant; and / or The water-soluble anionic dispersant includes at least one of triethanolamine lauryl sulfate, ammonium lauryl sulfate and triethanolamine polyoxyethylene alkyl ether sulfate; and / or The water-soluble nonionic dispersant includes at least one of polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene higher alcohol ether and polyoxyethylene octylphenyl ether.

8. A method for preparing the silicon dioxide polishing liquid according to any one of claims 1 to 7, characterized in that: include: mixing silane with a first inorganic solvent so that the silane is hydrolyzed to obtain a gel; mixing the gel with a base to obtain mesh particles; connecting spherical particles to the surface of the mesh particles to obtain silica composite particles; The silica composite particles are mixed with an oxidant, a pH adjuster, a dispersant, and a second inorganic solvent to obtain the silica polishing liquid.

9. The method according to claim 8, characterized in that The silane comprises at least one of tetramethoxysilane, tetraethoxysilane and tetrabutoxysilane; and / or The mass concentration of the silane in the first inorganic solvent is 3% to 12%; and / or The base comprises at least one of potassium hydroxide, sodium hydroxide, ammonia water, tetramethylammonium hydroxide, tetraethylammonium hydroxide, triethanolamine, diethanolamine, triethylamine, ethylenediamine, triethylenediamine, pyridine and 3-ethoxypropylamine; and / or The molar ratio of the base to the silane is 3:100 to 16:

100.

10. The method according to claim 8, characterized in that The gel satisfies at least one of the following conditions: The silane and the first inorganic solvent are mixed and first stirred, wherein the first stirring temperature is 15° C. to 50° C., the rotation speed is 100 rpm to 500 rpm, and the time is 0.5 h to 8 h; The viscosity of the gel is 10 mPas to 100 mPas.